2015
DOI: 10.3354/meps11460
|View full text |Cite
|
Sign up to set email alerts
|

Multi-population analysis of Puget Sound steelhead survival and migration behavior

Abstract: Until recently, research on mortality of anadromous fishes in the marine environment was largely limited to estimates of total mortality and association with group characteristics or the environment. Advances in sonic transmitter technology now allow estimates of survival in discrete marine habitats, yielding important information on species of conservation concern. Previous telemetry studies of steelhead Oncorhynchus mykiss smolts in Puget Sound, Washington, USA indicated that approx. 80% of fish entering mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 49 publications
3
56
4
Order By: Relevance
“…While other studies have shown that hatchery and wild salmonids have different smolt survival patterns (Moore et al 2015;Raymond 1988;Zimmerman et al 2015), our MARSS models did not support separating hatchery and wild steelhead populations (⌬AIC c > 14 for the best of these models). This may be due to the lack of long-term wild steelhead smolt survival time series for all geographic areas.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…While other studies have shown that hatchery and wild salmonids have different smolt survival patterns (Moore et al 2015;Raymond 1988;Zimmerman et al 2015), our MARSS models did not support separating hatchery and wild steelhead populations (⌬AIC c > 14 for the best of these models). This may be due to the lack of long-term wild steelhead smolt survival time series for all geographic areas.…”
Section: Discussioncontrasting
confidence: 92%
“…This may be due to the lack of long-term wild steelhead smolt survival time series for all geographic areas. While no consistent differences in early marine survival (survival during the first few weeks in the ocean) of wild versus hatchery-reared BC steelhead were reported (Welch et al 2011), a similar study on Washington State fish showed higher early marine survival for wild fish (Moore et al 2015).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations